Monitoring persistent organic chemicals in Antarctica in support of global chemical policy: a horizon scan of priority actions and challenges - Bengtson Nash, Susan; Bohlin-Nizzetto, Pernilla; Galban-Malagon, Cristobal; Corsolini, Simonetta; Cincinelli, Alessandra; Lohmann, Rainer (The Lancet Planetary Health, 2023)
Summary Global production and emission of chemicals exceeds societal capacities for assessment and monitoring. This situation calls for improved chemical regulatory policy frameworks and increased support for expedited decision making within existing frameworks. The polar regions of the Earth represent unique sentinel areas for the study of global chemical behaviour, and data arising from these areas can strengthen existing policy frameworks. However, chemical pollution research and monitoring in the Antarctic is underdeveloped, with geopolitical complexities and the absence of legal recognition of international chemical policy serving to neutralise progress made in other global regions. This Personal View represents a horizon scan by the action group Input Pathways of Persistent Organic Pollutants to Antarctica, of the Scientific Committee for Antarctic Research. Four priority research and research facilitation gaps are outlined, with recommendations for Antarctica Treaty parties for strategic action against these priorities.
Keywords: Antarktis; Sørishavet; forskning; forvaltning; helse; miljøgifter

Communicating the best available science to inform Antarctic policy and management: a practical introduction for researchers - Hughes, Kevin A.; Lowther, Andrew; Gilbert, Neil; Waluda, Claire M.; Lee, Jasmine R. (Antarctic Science, 2023)
Communication at the science-policy interface can be bewildering not only for early-career researchers, but also for many within the research community. In the context of Antarctica and the Southern Ocean, decision-makers operating within the Antarctic Treaty System (ATS) aspire to use the best available science as a basis for their decision-making. Therefore, to maximize the impact of Antarctic Treaty Parties' substantial investment in southern polar research, researchers wishing to contribute to policy and management must understand 1) how their work relates to and can potentially inform Antarctic and/or global policy and 2) the available mechanisms by which their research can be communicated to decision-makers. Recognizing these needs, we describe the main legal instruments relevant to Antarctic governance (primarily the ATS) and the associated meetings and stakeholders that contribute to policy development for the region. We highlight effective mechanisms by which Antarctic researchers may communicate their science into the policy realm, including through National Delegations or the Scientific Committee on Antarctic Research (SCAR), and we detail the key contemporary topics of interest to decision-makers, including those issues where further research is needed. Finally, we describe challenges at the Antarctic science-policy interface that may potentially slow or halt policy development.
Edition: 2023/10/18 Publisher: Cambridge University Press
Keywords: Antarktis; Antarktistraktaten; Sørishavet; forskning; forvaltning; kommunikasjon

Threat management priorities for conserving Antarctic biodiversity - Lee, Jasmine R.; Terauds, Aleks; Carwardine, Josie; Shaw, Justine D.; Fuller, Richard A.; Possingham, Hugh P.; Chown, Steven L.; Convey, Peter; Gilbert, Neil; Hughes, Kevin A.; McIvor, Ewan; Robinson, Sharon A.; et al. (PLOS Biology, 2022)
Antarctic terrestrial biodiversity faces multiple threats, from invasive species to climate change. Yet no large-scale assessments of threat management strategies exist. Applying a structured participatory approach, we demonstrate that existing conservation efforts are insufficient in a changing world, estimating that 65% (at best 37%, at worst 97%) of native terrestrial taxa and land-associated seabirds are likely to decline by 2100 under current trajectories. Emperor penguins are identified as the most vulnerable taxon, followed by other seabirds and dry soil nematodes. We find that implementing 10 key threat management strategies in parallel, at an estimated present-day equivalent annual cost of US$23 million, could benefit up to 84% of Antarctic taxa. Climate change is identified as the most pervasive threat to Antarctic biodiversity and influencing global policy to effectively limit climate change is the most beneficial conservation strategy. However, minimising impacts of human activities and improved planning and management of new infrastructure projects are cost-effective and will help to minimise regional threats. Simultaneous global and regional efforts are critical to secure Antarctic biodiversity for future generations.
Publisher: Public Library of Science
Keywords: Antarktis; biodiversitet; forvaltning; pingviner

Ant-ICON - ‘Integrated Science to Inform Antarctic and Southern Ocean Conservation’: a new SCAR Scientific Research Programme - Hughes, Kevin A.; Santos, Mercedes; Caccavo, Jilda A.; Chignell, Stephen M.; Gardiner, Natasha B.; Gilbert, Neil; Howkins, Adrian; Van Vuuren, Bettine Jansen; Lee, Jasmine R.; Liggett, Daniela; Lowther, Andrew; Lynch, Heather; et al. (Antarctic Science, 2022)
Antarctic and Southern Ocean environments are facing increasing pressure from multiple threats. The Antarctic Treaty System regularly looks to the Scientific Committee on Antarctic Research (SCAR) for the provision of independent and objective advice based on the best available science to support decision-making, policy development and effective environmental management. The recently approved SCAR Scientific Research Programme Ant-ICON - ‘Integrated Science to Inform Antarctic and Southern Ocean Conservation‘ - facilitates and coordinates high-quality transdisciplinary research to inform the conservation and management of Antarctica, the Southern Ocean and the sub-Antarctic in the context of current and future impacts. The work of Ant-ICON focuses on three research themes examining 1) the current state and future projections of Antarctic systems, species and functions, 2) human impacts and sustainability and 3) socio-ecological approaches to Antarctic and Southern Ocean conservation, and one synthesis theme that seeks to facilitate the provision of timely scientific advice to support effective Antarctic conservation. Research outputs will address the most pressing environmental challenges facing Antarctica and offer high-quality science to policy and advisory bodies including the Antarctic Treaty Consultative Meeting, the Committee for Environmental Protection and the Scientific Committee of the Commission for the Conservation of Antarctic Marine Living Resources.
Edition: 2022/12/02 Publisher: Cambridge University Press
Keywords: Antarktis; Antarktistraktaten; Sørishavet; forvaltning; human impact; miljøvern

Current logistical capacity is sufficient to deliver the implementation and management of a representative Antarctic protected area system - Hughes, Kevin A; Grant, Susie M (Polar Research, 2018)
Antarctica’s terrestrial ecosystems are vulnerable to impacts resulting from climate change and local human activities. The Antarctic Treaty System (ATS) provides for the designation of protected areas through the Protocol on Environmental Protection to the Antarctic Treaty. Unsystematic use of agreed management tools, including Antarctic Specially Protected Areas (ASPAs), has resulted in a protected area system lacking representation across the full range of Antarctic terrestrial ecosystems and Antarctic Conservation Biogeographic Regions (ACBRs). Systematic Conservation Planning (SCP) methods provide established mechanisms to fulfil ATS protected area designation goals. However, how would a continent-wide ASPA system be delivered should appropriate sites be identified using SCP or other methods? Although the rate of area protection has slowed recently, we show that newer Consultative Parties to the Antarctic Treaty are increasingly active as ASPA proponents and may have scope for further engagement with protected area management activities. Furthermore, all 16 ACBRs were found to be within the operational footprint of at least two Parties, indicating that this current logistical footprint could support the implementation and management of a continent-wide ASPA system. Effective management of a representative Antarctic protected areas system could be delivered through greater participation by those Parties with currently more limited protected area management responsibilities and greater use of remote-sensing technologies for protected area monitoring, where appropriate. Crucially, political will to implement an ASPA system identified through SCP approaches may be greater once a pragmatic means of delivery and effective management has been identified.
Keywords: Antarktis; Antarktistraktaten; biodiversitet; forvaltning; klimaendringer; menneskelig påvirkning; miljøvern; områdevern; økosystemer

Norske interesser og politikk for Bouvetøya - [s.n.] (Justis- og beredskapsdepartementet, 2015)
Helt siden Bouvetøya ble norsk biland i 1930 har denne øya langt sør i Atlanterhavet vært del av vår polare identitet og historie. Gjennom tidene har øya likevel ikke vært gjenstand for stor oppmerksomhet. Siden 1930 har det heller ikke vært gitt noen samlet omtale til Stortinget av forhold som angår forvaltningen av dette området. Regjeringen mener det nå er tid for å gjøre Bouvetøya bedre kjent gjennom en melding til Stortinget. Denne meldingen har derfor som mål å beskrive Bouvetøya, og gi en bred fremstilling av ulike forhold når det gjelder rettslige rammebetingelser, forvaltning og aktivitet på øya og i havområdene rundt. Regjeringen fremmer også en melding til Stortinget som omhandler norske interesser og politikk i Antarktis, herunder de norske bilandene Dronning Maud Land og Peter I Øy, heretter omtalt som Antarktismeldingen. 1 Tradisjonelt har de tre bilandene Bouvetøya, Dronning Maud Land og Peter I Øy vært omtalt sammen. Bouvetøya ligger nord for Antarktistraktatens virkeområde, og er ubestridt norsk territorium. Regjeringen har derfor funnet det hensiktsmessig å legge frem en egen melding om norske interesser og politikk for Bouvetøya. Spørsmål som gjelder Bouvetøya håndteres som en integrert del av norsk politikk. Dette inne- bærer å gjøre norsk lovgivning gjeldende for øya i den grad det er hensiktsmessig, og å sørge for at lovgrunnlaget er tilpasset behovene. I denne meldingen om Bouvetøya beskrives intern lovgivning så vel som det folkerettslige rammeverket, og ret- tighetene og pliktene som følger av dette, herunder retten til naturressurser og plikten til å ta vare på miljøet. Det gis en egen omtale av de stats- rettslige sidene ved øya, og av at det vil bli vurdert om disse og andre forhold bør reguleres i en egen lov.
Tilråding fra Justis- og beredskapsdepartementet 12. juni 2015, godkjent i statsråd samme dag. (Regjeringen Solberg)
Keywords: Bouvetøya; forvaltning; lovgivning; overvåking; politikk; økonomi

Norske interesser og politikk i Antarktis - Utenriksdepartementet (2015)
Publisher: Fagbokforlaget Place: Oslo
Keywords: Dronning Maud Land; forvaltning; politikk

Norway in the Antarctic - Rognhaug, Magnus Hovind (ed.) (Norsk Polarinstitutt, Norge Utenriksdepartementet, 2014)
Keywords: Antarktis; Antarktistraktaten; Bouvetøya; Dronning Maud Land; Norge; Peter I. Øy; ekspedisjoner; forskningsstasjoner; forvaltning; hvalfangst; klima; klimaendringer; miljø; naturressursforvaltning; naturvitenskapelig; polarforskning; polarområdene

Fornuft og følelser? : forståelser og forvaltning av hval og hvalfangst - Haugdahl, Morten (Norges teknisk-naturvitenskapelige universitet, 2013)
Norge hadde en dominerende posisjon i fortidas industrielle hvalfangst, og har også hatt en viktig rolle i konfliktene omkring den gjenværende fangsten av hval i dag. Hvalene har i løpet av denne tiden gått fra å være objekter i et økonomisk ”eventyr”, til å bli symbol for miljøbevissthet, hvor kampen om hvalfangsten har blitt framstilt som den definerende globale miljøkonflikten siden 1970-tallet. I denne avhandlingen blir endringer i forståelser av hvalen og hvalfangsten gjennom den moderne hvalfangstens historie undersøkt. Avhandlingen viser hvordan endringene kom til uttrykk i forvaltning, men også i norsk og internasjonal offentlighet, slik som i medier og i populærkultur. Teoretisk og metodisk har arbeidet gjort bruk av innrammingsbegrepet. Avhandlingen bruker i så måte innramming for å vise hvordan oppfatninger av hvalen og hvalfangsten har blitt fremstilt, forhandlet og ført til nye innramminger, og hvordan ulike forståelser og prosesser enkelte ganger har eksistert side ved side og i konflikt. For eksempel rammes hvalen inn som en økonomisk ressurs, som økologiske bestander som risikerer utryddelse, og som sansbare og sansende medskapninger. De ulike innrammingene fører igjen til vektlegging av ulike hensyn, men også til ulike former for kunnskap og forvaltning. Norway had a dominant role in the industrial whaling of the past, but has also had a central position in the conflicts around the remaining whaling of today. From being prized objects in an economic “adventure” whales have become a symbol of environmental awareness, and the disagreements on whaling has sometimes been perceived as the definite global environmental conflict since the 1970’s. This dissertation examines changes in understandings and management of whales and whaling through the history of modern whaling. The work shows how changes in perceptions of the whale have affected the administrative bodies of whaling and developed in Norwegian and international public debate, as in media and popular culture. Theoretically and methodically this work leans on the concept of “framing”. The dissertation uses framing to show how changes in the perception of whaling have been negotiated, leading to new framings of whales and whaling, and how some of these different understandings and processes have existed side by side, often in conflict with each other. The whale is for example at the same time framed as an economic resource, as scarce ecological stocks in risk of extinction, and as perceptible and sentient fellow beings. These frames lead to different considerations and emphasis, but also to different types of knowledge and management
Publication Title: Det humanistiske fakultet, Institutt for tverrfaglige kulturstudier Volume: Philosophiae doctor Issue: 2013:123 ISBN: 9788247143483
Keywords: Sørishavet; bioetikk; dyrevelferd; forvaltning; hvalfangst; hvalfangstkommisjonen; internasjonale; kulturstudier; miljøvern

Forskrift om miljøvern og sikkerhet i Antarktis - miljødepartementet, Klima- og (Lovdata, 2013)
Volume: 2013-04-26-412 Place: Oslo
Keywords: Antarktis; Dronning Maud Land; forurensning; forvaltning; jus; miljøvern; naturvern

Leadership in politics and science within the Antarctic Treaty - Dudeney, John R; Walton, David W H (Polar Research, 2012)
For over 50 years the Antarctic has been governed through the Antarctic Treaty, an international agreement now between 49 nations of whom 28 Consultative Parties (CPs) undertake the management role. Ostensibly, these Parties have qualified for their position on scientific grounds, though diplomacy also plays a major role. This paper uses counts of policy papers and science publications to assess the political and scientific outputs of all CPs over the last 18 years. We show that a subset of the original 12 Treaty signatories, consisting of the seven claimant nations, the USA and Russia, not only set the political agenda for the continent but also provide most of the science, with those CPs producing the most science generally having the greatest political influence. None of the later signatories to the Treaty appear to play a major role in managing Antarctica compared with this group, with half of all CPs collectively producing only 7% of the policy papers. Although acceptance as a CP requires demonstration of a substantial scientific programme, the Treaty has no formal mechanism to review whether a CP continues to meet this criterion. As a first step to addressing this deficiency, we encourage the CPs collectively to resolve to hold regular international peer reviews of their individual science programmes and to make the results available to the other CPs. Keywords: Governance; claimant states; Antarctic policy; scientific publications.
Keywords: Antarktis; Antarktistraktaten; forvaltning; politikk; vitenskap

Perspective: Strategic challenges of tourism development and governance in Antarctica: taking stock and moving forward - Lamers, Machiel; Liggett, Daniela; Amelung, Bas (Polar Research, 2012)
Keywords: Antarktis; forvaltning; turisme

Norge i Antarktis : fra erobring til moderne forskning - Winther, Jan-Gunnar; Andersen, Rolf Trolle; Basberg, Bjørn L; Bomann-Larsen, Tor; Haugland, Jan Erling; Njåstad, Birgit; Orheim, Olav; Tveraa, Torkild; Monsen, Oddbjørn (Schibsted, 2008)
Keywords: Antarktis; Norge; ekspedisjoner; forskningsstasjoner; forvaltning; hvalfangst; klima; klimaendringer; miljø; naturressursforvaltning; naturvitenskapelig; polarforskning; polarområdene

Norway in the Antarctic : from conquest to modern science - Winther, Jan-Gunnar; Tveraabak, Jacob; Andersen, Rolf Trolle; Basberg, Bjørn L; Bomann-Larsen, Tor; Haugland, Jan Erling; Njåstad, Birgit; Orheim, Olav; Monsen, Oddbjørn; Goldman, Helle V (Schibsted, 2008)
Keywords: Antarktis; Norge; ekspedisjoner; forskningsstasjoner; forvaltning; hvalfangst; klima; klimaendringer; miljø; naturressursforvaltning; naturvitenskapelig; polarforskning; polarområdene

Forskrift om grunnlinjen for sjøterritoriet ved Bouvetøya - Utenriksdepartementet (Lovdata, 2005)
Volume: 2005-02-25-174 Place: Oslo
Keywords: Bouvetøya; forvaltning; jus

Antarktis : norsk natur- og kulturminneforvaltning - Njåstad, Birgit (ed.) (Norsk Polarinstitutt, 1999)
Publication Title: Norsk Polarinstitutt. Rapportserie
Keywords: Antarktis; Norge; forvaltning; kulturminneforvaltning; miljøvern; naturforvaltning; naturvern; polarområdene

Conservation status of Bouvetøya - Sømme, Lauritz (Progress in conservation of the Subantarctic islands: proceedings of the SCAR/IUCN Workshop on Protection, Research and Management of Subantarctic Islands, Paimpont, France, 27-29 April 1992, 1995)
Issue: 2
Keywords: Bouvetøya; forvaltning; natur

Subantarctic island research: discussion and recommendations - Sømme, Lauritz (Progress in conservation of the Subantarctic islands: proceedings of the SCAR/IUCN Workshop on Protection, Research and Management of Subantarctic Islands, Paimpont, France, 27-29 April 1992, 1995)
Issue: 2
Keywords: Sørishavet; forskning; forvaltning; natur

The regulation of Antarctic tourism: a study in regime effectiveness - Herr, Richard A; Davis, Bruce W (Fridtjof Nansen institutt, 1993)
Publication Title: IARP publication series
Keywords: Antarktis; forvaltning; turisme

Bouvetøya: et norsk naturreservat - Sømme, Lauritz (Fauna, 1992)
Keywords: Bouvetøya; fauna; forvaltning; natur

Samtykke til ratifikasjon av Protokoll om miljøvern til Antarktistraktaten, undertegnet i Madrid 4. oktober 1991 - Utenriksdepartementet (1992)
Pages: 64 Place: Oslo
Keywords: Antarktis; forvaltning; miljøvern; politikk

The Antarctic treaty system in world politics - Jørgensen-Dahl, Arnfinn (Red.); Østreng, Willy (Red.) (Macmillan in association with The Fridtjof Nansen Institute, 1991)
Keywords: Antarktis; Antarktistraktaten; forvaltning; havrett; internasjonalt samarbeid; miljø; naturressurser; polarområdene; politikk; ressurser; rett

Conference report: preservation or exploitation - Stokke, Olav Schram (Marine Policy, 1991)
Keywords: Sørishavet; forvaltning; jus; politikk

Symposium report: "The Antarctic Treaty System in World Politics" - Stokke, Olav Schram (International Challenges, 1991)
Keywords: Antarktis; Sørishavet; forvaltning; jus; politikk

Negtiationg a new regime: how CRAMRA came into existence - Andersen, Rolf Trolle (International Challenges, 1990)
Keywords: Antarktis; forvaltning; historie; mineraler; politikk

Protection of the environment in Antarctica: are present regimes sufficient? - Barnes, James N (International Challenges, 1990)
Keywords: Antarktis; forvaltning; miljøvern

The practical implications of the eco-system approach in CCAMLR - Beddington, John R; Basson, M; Gulland, J A (International Challenges, 1990)
Keywords: Sørishavet; forvaltning; økologi

Consultative status under the Antarctic Treaty: redefining the criteria? - Bos, Adrian (International Challenges, 1990)
Keywords: Antarktis; forvaltning; politikk

The design of CRAMRA: how appropriate for the protection of the environment? - Brown, Alan D (International Challenges, 1990)
Keywords: Antarktis; forvaltning; miljøvern; mineraler

Antarctica Treaty System: are there viable alternatives? - Falk, Richard (International Challenges, 1990)
Keywords: Antarktis; forvaltning; politikk

The ability of the Antarctic Treaty System to adapt to external challenges - Haron, Mohamed (International Challenges, 1990)
Keywords: Antarktis; forvaltning; politikk

The influence of the United Nations on the Antarctic system: a source of erosion or cohesion? - Harris, Stuart (International Challenges, 1990)
Keywords: Antarktis; forvaltning; politikk

Has CCAMLR worked? management policies and ecological needs - Heap, John A (International Challenges, 1990)
Keywords: Sørishavet; forvaltning; økologi

CRAMRA: the ugly duckling of the Antarctic Treaty System? - Joyner, Christopher C (International Challenges, 1990)
Keywords: Antarktis; forvaltning; miljøvern; mineraler

CRAMRA and other enviromental regimes in the ATS: how well does CRAMRA fit? - Kimball, Lee A (International Challenges, 1990)
Keywords: Antarktis; forvaltning; jus; miljøvern

Towards firmer institutionalization of the ATS? Future role of the consultative meeting and the issue of a permanent secretariat - Messer, Kurt (International Challenges, 1990)
Keywords: Antarktis; forvaltning; jus

Veien til CRAMRA: en studie av forhandlingene om opprettelsen av et mineralregime i Antarktis - Mørkved, Berit (Fridtjof Nansens institutt, 1990)
Publication Title: Fridtjof Nansens institutt. Studie R Volume: 1990:6
Keywords: Antarktis; forvaltning; mineraler; politikk

The implementation of CCAMLR: is the decision-making machinery conductive to good management? - Orrego Vicuña, Francisco (International Challenges, 1990)
Keywords: Sørishavet; forvaltning; miljøvern; politikk

SCAR in the ATS: conflict or harmony? - Rinaldi, Carlos (International Challenges, 1990)
Keywords: Antarktis; forskning; forvaltning; politikk

Resource management and the changing profile of science in Antarctica: a growing pressure for relevance? - Scully, Richard Tucker (International Challenges, 1990)
Keywords: Antarktis; forskning; forvaltning

Forholdet mellom vitenskap og politikk i internasjonal ressursforvaltning: det internasjonale samarbeid om forvaltning av de levende marine ressurser i Antarktis - Indreeide, Thor Vidar (Fridtjof Nansens institutt, 1989)
Publication Title: Fridtjof Nansens institutt. Studie R
Keywords: Antarktis; Sørishavet; forskning; forvaltning; politikk; ressurser

The relationship between science and politics in international management of marine living resources: the case of CCAMLR - Indreeide, Thor Vidar (International Challenges, 1989)
Keywords: Antarktis; Sørishavet; forvaltning; jus; politikk

En fremtid i Antarktis? - Andersen, Rolf Trolle (Dialog Norge-Sverige: konferanser i Norges ambassade, Stockholm. 2: polarområdene, hvite felt i politikk og vitenska, 1988)
Keywords: Antarktis; forvaltning; mineraler; politikk

Utviklingen i internasjonal forvaltning av hval 1975-1985: politisk mobilisering, økonomisk marginalisering - Hoel, Alf Håkon (Fridtjof Nansens institutt, 1986)
Publication Title: Fridtjof Nansens institutt. Studie R
Keywords: Sørishavet; forvaltning; hvalfangst

Ressursforvaltningen i Antarktis - konflikt eller samarbeid? - Antonsen, Per (Fridtjof Nansens institutt, 1984)
Publication Title: Fridtjof Nansens institutt. Studie R
Keywords: Antarktis; forvaltning; jus; ressurser

Scientific research and cooperation in Antarctica - Gjelsvik, Tore (Antarctic challenge: conflicting interests, cooperation, environmental protection, economic development, 1984)
Keywords: Antarktis; forskning; forvaltning

Konvensjon om bevaring av marine levende ressurser i Antarktis = Convention on the Conservation of Antarctic Marine Living Resources (Lovdata, 1980)
Place: Oslo
Keywords: Sørishavet; forvaltning; jus; marinbiologi; miljøvern; naturvern

Trends and prospects for regimes for living and mineral resources in the Antarctic + discussion - Sollie, Finn (Law of the sea: neglected issues - proceedings, Law of the Sea Institute twelfth annual conference, October 23-26, 1978, The Hague, 1979)
Keywords: Antarktis; forvaltning; jus

Internasjonal regulering av hvalfangsten: et tilbakeblikk og en vurdering - Ruud, Johan T (Samtiden, 1956)
Keywords: Sørishavet; forvaltning; historie; hvalfangst; politikk

Modern whaling and its prospects - Ruud, Johan T (Norsk hvalfangst-tidende, 1952)
Keywords: Sørishavet; forvaltning; hvaler; hvalfangst

Norway's Antarctic research activities: report to SCAR - Norsk Polarinstitutt; Polarinstitutt, Norsk (Norwegian Polar Institute)
Volume: Årlig rapport
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; forskning; forvaltning